A systematic review and meta‐analysis on the influence of biological implant surface coatings on periimplant bone formation. Issue 11 (4th July 2016) - Jenny, Gregor; Jauernik, Johanna; Bierbaum, Susanne; Bigler, Martin; Grätz, Klaus W.; Rücker, Martin; Stadlinger, Bernd
Abstract: This systematic review and meta‐analysis evaluated the influence of biological implant surface coatings on periimplant bone formation in comparison to an uncoated titanium reference surface in experimental large animal models. The analysis was structured according to the PRISMA criteriae. Of the1077 studies, 30 studies met the inclusion criteriae. Nineteen studies examined the bone implant contact (BIC) and were included in the meta‐analysis. Overall, the mean increase in BIC for the test surfaces compared to the reference surfaces was 3.7 percentage points (pp) (95% CI −3.9–11.2, p = 0.339). Analyzing the increase in BIC for specific coated surfaces in comparison to uncoated reference surfaces, inorganic surface coatings showed a significant mean increase in BIC of 14.7 pp (95% CI 10.6–18.9, p < 0.01), extracellular matrix (ECM) surface coatings showed an increase of 10.0 pp (95% CI 4.4–15.6, p < 0.001), and peptide coatings showed a statistical trend with 7.1 pp BIC increase (95% CI −0.8–15.0, p = 0.08). In this review, no statistically significant difference could be found for growth factor surface coatings (observed difference −3.3 pp, 95% CI −16.5–9.9, p = 0.6). All analyses are exploratory in nature. The results show a statistically significant effect of inorganic and ECM coatings on periimplant bone formation. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2898–2910, 2016.